Gemological and chemical characteristics of green tourmaline from Madagascar, Mozambique, and Tanzania - Kaewtip M. (2017)
© 2016, Walailak University. All rights reserved. Green tourmalines from Madagascar, Mozambique, and Tanzania were investigated for their gemological properties, spectroscopic characteristics, and chemical compositions. The studied specimens were green, bluish green, yellowish green to brownish green, greenish blue, and blue. Their gemological properties were in a typical range of natural tourmaline. Microscopic examination displayed internal features which were normal of inclusion in tourmaline, such as growth tubes, hollow tubes, healed fractures, fluid inclusions, 2-phase (liquid-gas) inclusions, and small fractures. The cause of coloration in green tourmaline was examined by observing their Ultraviolet-visible-near infrared (UV-Vis-NIR) absorption spectra. The samples from Madagascar and Mozambique exhibited the same spectral range. The absorption bands at near 332, 385, 400 and 415 nm were related to Mn 2+ from d-d transitions at the octahedral site. The intensity of absorption bands at 720 and 732 nm were attributed to Fe 2+ -Fe 3+ intervalence charge transfer (IVCT), while strong bands between 918 to 1220 nm were associated with the Fe 2+ octahedral in the Y site. The samples from Tanzania displayed absorption spectra at 307 to 628 nm due to V 3+ on the octahedral sites (Z-sites) and a weak peak at 417 nm associated with Cr 3+ . The green tourmalines from this study exhibit intense bands around 1425 nm that are attributed to hydroxyl groups. Fourier Transform Infrared (FTIR) absorption spectra in the range 4000-500 cm -1 were used to identified the stretching vibration of Si 6 O 18 rings (1200-820 cm -1 ) and the BO 3 (1350 to 1250 cm -1 ) and hydroxyl groups (3700 to 3400 cm -1 ) in the structure of tourmaline. Chemical analyses from electron probe micro-analysis (EPMA) revealed that samples from Madagascar and Mozambique had chemical compositions of elbaite end-members (lower in Ca content and richer in Na content), whereas the samples from Tanzania (Ca-Mg rich tourmaline) were of uvite end-members. This study proposes chemical fingerprinting by the Laser Ablation-Inductively coupled plasma-mass spectroscopy (LA-ICP-MS) technique, useful for differentiating green tourmalines from 3 different localities. The Madagascar samples contained Li, Fe, Zn, Ga, Sn, Pb and Bi, the Mozambique samples contained Li, Fe, Zn and Sn, and the Tanzania tourmalines contained Ti, V, Cr and Sr.